PENDIDIKAN KARAKTER SEBAGAI STRATEGI MENCEGAH PERILAKU BULLIYING DI SEKOLAH DASAR - Arni, Arni; Putri, Vivin Avania; Yusriani, Yusriani (Universitas Sulawesi Tenggara, 2023)
Bullying behavior in elementary schools is becoming an increasingly disturbing problem, because it has a negative impact on students' mental health and social-emotional development. Character education can serve as an effective prevention strategy to address the phenomenon of bullying among students. Through the development of good character values, such as empathy, respect, responsibility, and justice, students are expected to be able to reduce bullying behavior. This study aims to examine the role of character education in preventing bullying behavior in elementary schools through an in-depth literature study. The results of the study indicate that character education that is consistently applied can create a safe, inclusive, and supportive learning environment, which reduces the incidence of bullying.